Programming with Multiple Precision - Nikolaevskaya, Elena; Khimich, Alexandr; Chistyakova, Tamara; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
GMP and MPFR are portable libraries for arbitrary precision arithmetic, large set of functions which allows to organize the computational process with different digit capacity. This book is a real guide for writing programs in C/C++ using the GMP and MPFR libraries to improve the accuracy of the solutions, including in parallel programming. The book contains many examples of the program code with its experiments results. It will be interesting for many scientists, programmers and students, who want to study programming, improve or expand their level programming. The book is useful for graduates in computer science and mathematics (perhaps too specialized for the most of undergraduates, at least in its present state), researchers in Numerical Analysis, Computer Algebra and developers of the multiple-precision libraries.
Part I The usage GMP and MPFR in C/C++ -- Why does the precision improve?- About GMP -- Solution of linear algebraic equations by Gauss method -- What is MPFR? -- GMP for (Ns(B++ -- Part II Parallel programming with GMP -- Parallel calculations using MPI -- MPIBNCpack Library -- Parallel method for solution SLAE with multiply precision.s
Keywords: Engineering; Computer science; Engineering; Computational Intelligence; Programming Techniques